Multi-disciplinary research team approach to recruiting patients, close persons and healthcare professionals in hospices. Issue 3 (1st September 2016) - Armour, Kathy; Campbell, Cathy L; Bailey, Cara; Kinghorn, Philip; Orlando, Rosanna; Perry, Rachel; Jones, Louise; Coast, Joanna
Abstract : Introduction: There are several well-known barriers to conducting research in hospices. Hospices may lack experience of research and have less developed governance procedures. The vulnerability of patients and the sensitivity of the topic may also form real, or perceived, barriers. Recruitment of participants to end-of-life projects therefore tends to be slow and resource intensive. It requires clear communication between academic researchers and hospice staff. Aim: To establish a multi-disciplinary team (MDT) approach to enhance research in a voluntary-sector hospice incorporating day services, outpatient clinical services and inpatient unit. Method: An integrated multi-disciplinary research team (MDRT) was created comprising four sub-teams: the hospice team including a dedicated research lead, the university team, a wider project group and an external advisory group. Seventy-two participants: 33 patients, 21 close persons and 17 healthcare professionals were recruited to a semi-qualitative research study between October 2012 and February 2014. Challenges to recruitment were identified and solutions applied during the course of the study by the MDRT. Results: Key members of the MDRT, identified early in the research process, enabled recruitment difficulties to be overcome. Approaches included increasing the visibility of researcher, increasing and regularising communication between core MDRT team members and maintaining ongoing dialogue with potential participants to reduce staff gatekeeping. Conclusion: Simulating a clinical MDT-style working approach can facilitate palliative care research activity. Creating a research-supportive environment identifies problems and creates solutions. The MDRT model is offered to researchers and hospice staff to develop and enact effective participant recruitment to build end-of-life research. Reference: Bailey C, Kinghorn P, Orlando R, et al . The ICECAP-SCM tells you more about what I am going through: A think-aloud study measuring quality of life among: patients receiving supportive and palliative care. Palliat Med 2016;30 (7):642–652